Issue of education about sexuality in schools in the countries of Sub-Saharan Africa : The example of Cameroon - (:unkn) unknown (My University, 2012)
Education on sexuality or “sex education” aims to reduce risky sexual behaviour amongadolescents and young adults in particular. Several international organisations (UNESCO,WHO, UNAIDS, UNICEF) encourage sex education in schools, particularly in countries ofsub-Saharan Africa where sexually transmitted infections (STI) and HIV/Aids remainfrequent. However the lack of literature on sex education in schools makes implementing suchpolicies difficult. Developing sex education in schools of sub-Saharan Africa requires takinginto account the specific socio-Economic, cultural and institutional contexts of these countries,as well as the individual conceptions that young people have of sexuality and whichdetermine their sexual behaviour. Teacher involvement in this task is not evident either, asteachers tend to resist implementing sex education for various reasons that should beidentified and analyzed.These PhD thesis studies pupil conceptions of sex education and the needs they identify inthis domain on one hand, and the conceptions and professional practices of teachers in sexeducation on the other hand, in the country of Cameroon. With the purpose of contributing thedevelopment of theoretical models of intervention and a framework for teacher training in sexeducation adapted to the African context, our research attempts to identify the factors thataffect the implementation and the success of sex education in sub-Saharan Africa via the caseof Cameroon. Our study is based on a survey of middle-School pupils (n=3071) and a surveyof general education teachers (n=368) in Cameroon.Results show that pupil individual conceptions are favourable to sex education in schools, andthat pupils consider their teachers and their schools to be legitimate providers of sexeducation. Pupils rarely discuss sexuality with their parents, whereas their main sources ofinformation on sexuality are the television, school, and the internet. The pupils expressededucational needs enco
Keywords: African Research